Craniofacial characteristics of Caucasian and Afro-Caucasian Brazilian subjects with normal occlusion - Guilherme Janson; Camila Leite Quaglio; Arnaldo Pinzan; Eduardo Jacomino Franco; Marcos Roberto de Freitas (Journal of Applied Oral Science, 2011)
OBJECTIVE: The objective of this study was to compare the skeletal, dental and soft tissue characteristics of Caucasian and Afro-Caucasian Brazilian subjects with normal occlusion and to evaluate sexual dimorphism within the groups. MATERIAL AND METHODS: The sample comprised lateral cephalograms of untreated normal occlusion subjects, divided into 2 groups. Group 1 included 40 Caucasian subjects (20 of each sex), with a mean age of 13.02 years; group 2 included 40 Afro-Caucasian subjects (20 of each sex), with a mean age of 13.02 years. Groups 1 and 2 and males and females within each group were compared with t tests. RESULTS: Afro-Caucasian subjects presented greater maxillary protrusion, smaller upper anterior face height and lower posterior face height, larger upper posterior face height, greater maxillary and mandibular dentoalveolar protrusion as well as soft tissue protrusion than Caucasian subjects. The Afro-Caucasian female subjects had less mandibular protrusion and smaller total posterior facial height and upper posterior facial height than males. CONCLUSIONS: Brazilian Afro-Caucasian subjects have greater dentoalveolar and soft tissue protrusion than Brazilian Caucasian subjects, with slight sexual dimorphism in some variables.